Management of health care for patients with heart failure in the Northwestern, North Caucasian, Volga and Southern Federal Districts of the Russian Federation: 6-year changes and future prospects - N. E. Zvartau; S. V. Villevalde; A. O. Konradi; I. B. Tuaeva; A. S. Galyavich; A. V. Khripoun; A. E. Soloveva; G. V. Endubaeva; A. E. Medvedev; A. M. Erastov; M. V. Dubinina; D. N. Nedbaeva; et al. (Российский кардиологический журнал)
In connection with the increase in the prevalence and incidence of heart failure, the development of health care systems for patients with this disease in the constituent entities of the Russian Federation is relevant. Over the past 6 years, measures to improve the cardiology service have been implemented in the regions of the Northwestern, North Caucasian, Volga and Southern Federal Districts under the leadership of the Ministry of Health of the Russian Federation in cooperation with the National Medical Research Centers. Teams of chief non-staff cardiologists continue to actively participate in updating the regulatory framework, as well as expanding the programs of preferential medication provision as part of providing care to patients with heart failure. In some regions, organizational barriers remain, the elimination of which requires a comprehensive modernization of regional healthcare systems with the involvement of multidisciplinary teams.